Efektivitas Metode LGD Dalam Pembelajaran Siswa SMK Jurusan Teknik Elektronika Industri (TEI) - Fauzan, Bimo Rahman; Ramadhan, Gilang; Luthfi, Fuad; Abhinaya, R. Ahmad Faiz; Fua’din, Ahmad (Yayasan Daarul Huda Kruengmane, 2025)
The competitive job market requires enhancing the effectiveness of education in vocational high schools. In the Industrial Electronics Engineering program at SMK Negeri 1 Karawang, some students have low comprehension skills alongside very low motivation to learn. This research seeks to assess the impact of the Leaderless Group Discussion technique on improving students' learning results and engagement. The study was designed as a pre-experimental investigation incorporating a quantitative methodology, featuring a single group that underwent both a pretest and a posttest. Initially, questionnaires were distributed to pinpoint learning challenges, followed by the execution of a pretest, the application of case-based leaderless group discussions, and finally a posttest. Findings indicated an improvement in the average score from 6. 61 to 7. 69, along with an increase in the median score from 7 to 8. Beyond academic gains, there were notable improvements in student engagement, team collaboration abilities, and comprehension of previously challenging technical subjects. Participants expressed favorable experiences resulting from this initiative, particularly enjoying a more interactive and cooperative learning environment. The results of this effort include a research document, a scholarly article, and the possibility of wider application of this approach in vocational education. Consequently, the Leaderless Group Discussion method has been demonstrated to be an effective solution for tackling issues in contemporary vocational training.